Upaya Peningkatan Hasil Belajar Siswa Pada Pembelajaran Bola Voli Menggunakan Model Problem Based Learning Kelas IV SD IT Darussalam Bayan - Anjasmara, Indra; Khaq, Muflikhul; Putro, Sugeng Eko (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
This study aims to describe the application of the problem-based learning model and determine the increase in the psychomotor development of students. This study uses Classroom Action Research (CAR), which consists of two cycles. Each cycle consists of two meetings. Subjects in the research were 15 students of class IV SD IT Dasussalam Bayan consisting of 9 boys and 6 girls. Data collection methods used are interviews, observation and document analysis. Methods of data analysis using descriptive analysis. Based on the data analysis that has been carried out on the implementation of learning cycle I, it gets an average percentage of 77.30%. Meanwhile, in cycle II, the average percentage was 82.25%. So that in cycle II it is included in the very good category. Based on the results of student observations about the psychomotor development of students with the application of problem-based learning (PBL) models in the pre-cycle with an average of 52%, an average of 68.8% in the first cycle and 79.25% in the second cycle. Child development experienced an increase of 16.8% from pre-cycle to cycle I. Meanwhile, cycle I to cycle II was 10.45%. In cycle II with an average of 79.25%, it is in the very good category, thus the application of the problem-based learning model is suitable to be applied to improve students' psychomotor development.